Analysing the Role of Education in Shaping Students' Critical Thinking Starting from Elementary School - Djumat, Irwan; Rajaloa, Nani I.; Hasmawati, Hasmawati (Mimbar Sekolah Dasar, 2025)
The limited literacy and critical thinking skills of elementary school students in understanding media information can give rise to the spread of hoaxes. This research is considered urgent as it seeks to examine the critical thinking process in fostering social awareness from an early age. The purpose of this study is to analyze the design of learning strategies that can enhance students’ media literacy and critical thinking abilities. A quantitative approach was applied, involving a sample of 460 students from grades 4–6, selected through stratified random sampling from several elementary schools in Ternate City. Data were collected using a Likert-scale questionnaire ranging from strongly disagree (1) to strongly agree (5). The data were analyzed using descriptive statistics and regression techniques with the assistance of SPSS Version 29.0. The findings indicate that the implementation of social media-based education significantly improves students’ critical thinking skills in relation to media literacy. In conclusion, integrating social education with media literacy can help students develop the ability to think critically and act responsibly when evaluating information they read or encounter in the media. The study suggests the need for training programs and additional learning resources in elementary schools to strengthen these competencies. The practical implication is that students will increasingly develop the capacity to identify and understand valid information, thereby reducing susceptibility to misinformation.